2016
DOI: 10.1007/s10943-016-0307-7
|View full text |Cite
|
Sign up to set email alerts
|

Dare to Dream: Personal Values, Life Goals, and International Students in New Zealand

Abstract: It has been well identified and supported in the literature that values and life goals are associated with one's general well-being. However, there have been few studies on values and life goals among international students in New Zealand. This study addressed this lack of research by focusing on the life goals and personal values among international students in three tertiary institutes in New Zealand. Based on the literature review, the hypothesis of this study is that international students' intrinsic life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Studies of the relationships between religion and health in New Zealand have found weak correlations between religion, spirituality, and well-being (Zhang 2020 ; Hoverd and Sibley 2013 ). This extends to the relationship between religious belief and coping (Zhang and Zhang 2017 ; Krägeloh et al 2012 ). However, others have struggled to discern meaningful findings between secular and spiritual approaches to health in New Zealand (Lauricella 2016 ).…”
Section: Introductionmentioning
confidence: 82%
“…Studies of the relationships between religion and health in New Zealand have found weak correlations between religion, spirituality, and well-being (Zhang 2020 ; Hoverd and Sibley 2013 ). This extends to the relationship between religious belief and coping (Zhang and Zhang 2017 ; Krägeloh et al 2012 ). However, others have struggled to discern meaningful findings between secular and spiritual approaches to health in New Zealand (Lauricella 2016 ).…”
Section: Introductionmentioning
confidence: 82%
“…This benefit was not dependent on their sociocultural, financial, or professional status. Self-determined motivation to migrate can also protect against culture shock (Yang et al, 2018) and self-destructive behavior (Zhang & Zhang, 2017). The role of self-development goals is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…To measure Extrinsic Life Aspirations, participants completed the corresponding subscales of the Aspiration Index (Grouzet et al., 2005; Kasser & Ryan, 2001). The full index measures 11 aspirational domains and has been shown to be valid and reliable within the U.S., as well as across a number of other cultures and contexts (Davids & Roman, 2013; Martos & Kopp, 2012; Zhang & Zhang, 2017). The domains of the full index include: financial success, image, conformity, popularity, self‐acceptance, affiliation, community feeling, physical health, hedonism, safety, and spirituality.…”
Section: Methodsmentioning
confidence: 99%